Admittance of MIS structures based on graded‐gap MBE HgCdTe with Al2O3 insulator. Issue 7 (14th April 2016) - Voitsekhovskii, Alexander V.; Nesmelov, Sergey N.; Dzyadukh, Stanislav M.; Vasil`ev, Vladimir V.; Varavin, Vasiliy S.; Dvoretsky, Sergey A.; Mikhailov, Nikolay N.; Yakushev, Maxim V.; Sidorov, Georgiy Y.
Abstract: The paper presents the results of studies of the admittance of MIS structures based on heteroepitaxial MBE n ( p )‐Hg0.78 Cd0.22 Te with insulator coating SiO2 /Si3 N4 and Al2 O3 in the test signal frequency range 10 kHz‐1 MHz at temperatures ranging from 8 to 220 K. The main parameters of MIS structures with different insulators were determined. MIS structures with Al2 O3 have a large enough insulator capacitance (compared to SiO2 /Si3 N4 ), a significant modulation capacitance on the CV characteristics, high dielectric strength and low values of the flat‐band voltage. The effective charge density found from the value of the flat‐band voltage and slow interface trap density for structures with Al2 O3 comparable with the corresponding densities for structures with SiO2 /Si3 N4 . (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)